Manifestasi Klinis Covid-19 pada Kulit - Iswinarno Doso Saputro; Medisa Primasari (PT Dexa Medica, 2021)
Severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2) is a strain of coronavirus that causes Coronavirus Disease 2019 (Covid-19). The first case was reported in the city of Wuhan, China, through the consumption of bush meat which presumed to be the reservoir of the virus. Human-to-human transmission occurs through respiratory droplet inhalation or touching contaminated surfaces, then without washing hands, virus may enter the body through contact with mucous membrane in the eyes, nose, or mouth. Covid-19 manifested in various level of severity among individuals, from mild, severe, critical, or even symptom-free. Clinical manifestations are not specific and vary among individuals. Common symptoms are fever, cough, fatigue, shortness of breath, upper respiratory symptoms, gastrointestinal disorders, loss of taste or smell, also presentation of skin manifestation. Skin manifestation associated with Covid-19 also varies and may appear at different times without being followed by other symptoms. Laboratory tests, imaging test, and identification of genetic material of SARS-CoV-2 are necessary to confirm the diagnosis of COVID-19.